Integrated total pelvic floor ultrasound in pelvic floor defaecatory dysfunction. (January 2017) - Hainsworth, A. J.; Solanki, D.; Hamad, A.; Morris, S. J.; Schizas, A. M. P.; Williams, A. B.
Abstract: Aim: Imaging for pelvic floor defaecatory dysfunction includes defaecation proctography. Integrated total pelvic floor ultrasound (transvaginal, transperineal, endoanal) may be an alternative. This study assesses ultrasound accuracy for the detection of rectocele, intussusception, enterocele and dyssynergy compared with defaecation proctography, and determines if ultrasound can predict symptoms and findings on proctography. Treatment is examined. Method: Images of 323 women who underwent integrated total pelvic floor ultrasound and defaecation proctography between 2011 and 2014 were blindly reviewed. The size and grade of rectocele, enterocele, intussusception and dyssynergy were noted on both, using proctography as the gold standard. Barium trapping in a rectocele or a functionally significant enterocele was noted on proctography. Demographics and Obstructive Defaecation Symptom scores were collated. Results: The positive predictive value of ultrasound was 73% for rectocele, 79% for intussusception and 91% for enterocele. The negative predictive value for dyssynergy was 99%. Agreement was moderate for rectocele and intussusception, good for enterocele and fair for dyssynergy. The majority of rectoceles that required surgery (59/61) and caused barium trapping (85/89) were detected on ultrasound. A rectocele seen on both transvaginal and transperineal scanning was more likely to require surgery than if seen with only one mode ( P  = 0.0001). If there was intussusception on ultrasound the patient was more likely to have surgery ( P  = 0.03). An enterocele visualized on ultrasound was likely to be functionally significant on proctography ( P  = 0.02). There was, however, no association between findings on imaging and symptoms. Conclusion: Integrated total pelvic floor ultrasound provides a useful screening tool for women with defaecatory dysfunction such that defaecatory imaging can avoided in some.